2019
DOI: 10.1177/1524839918824078
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Evaluation of Culture Camps to Increase Alaska Native Youth Wellness

Abstract: Suicide is a significant health disparity among Alaska Native youth, which is linked to cultural disruptions brought about by colonialism and historical trauma. Many Indigenous suicide prevention efforts center on revitalizing and connecting youth to their culture to promote mental health and resilience. A common cultural approach to improve psychosocial outcomes is youth culture camps, but there has been little evaluation research to test this association. Here, we conduct a pilot evaluation of a 5-day cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 32 publications
0
34
0
Order By: Relevance
“…Fortunately, developing a sense of mattering can be highly protective in reducing suicidal tendencies (for a discussion, see Milner et al, 2016) and research is now beginning to explore the role of mattering in suicide prevention applications (see Barnett et al, 2020). One impetus for such efforts is a comprehensive survey of over 30,000 adolescents that found that perceived mattering in one's community is a key protective asset that mitigates planning for suicide (see Murphey et al, 2004).…”
Section: Mattering In the Real Worldmentioning
confidence: 99%
“…Fortunately, developing a sense of mattering can be highly protective in reducing suicidal tendencies (for a discussion, see Milner et al, 2016) and research is now beginning to explore the role of mattering in suicide prevention applications (see Barnett et al, 2020). One impetus for such efforts is a comprehensive survey of over 30,000 adolescents that found that perceived mattering in one's community is a key protective asset that mitigates planning for suicide (see Murphey et al, 2004).…”
Section: Mattering In the Real Worldmentioning
confidence: 99%
“…In a study to reduce obesity, Kelley and Lowe (2018) saw significantly better outcomes in measures of cultural identity, perceived stress, obesity knowledge, physical activity, and healthy eating behavior in American Indian youth who participated in their after-school, culture-based health education program with CTCs than a standard health education program. Culturalspecific interventions generally showed effectiveness, especially with the youth (Barnett et al, 2020;Boyd-Ball et al, 2006;Goodkind et al, 2010). Some studies were program evaluations conducted to maximize the potential for providing Indigenous-centered care.…”
Section: Addressing Historical Trauma Through Interventions and Programsmentioning
confidence: 99%
“…The studies selected for inclusion from the literature had a variety of different methods used to collect data. There were 26 that followed a primarily qualitative research design (Bruner et al, 2019 ; Fraser et al, 2015 ; Freeman, 2017 ; Goodkind et al, 2012 ; Hatala et al, 2017 , 2019 , 2020 ; Isaacson, 2018 ; Kral et al, 2014 ; Krieg, 2016 ; McMahon et al, 2013 ; Morton et al, 2020 ; Njeze et al, 2020 ; Ranahan & Yuen, 2017 ; Rasmus et al, 2014 ; Sasakamoose et al, 2016 ; Strickland & Cooper, 2011 ; Trout et al, 2018 ; Ulturgasheva et al, 2014 ; Ungar et al, 2008 ; Victor et al, 2016 ; Wexler, 2014 ; Wexler et al, 2013 , 2014 , 2016 ; Wood et al, 2018 ); 8 followed a quantitative design (Ames et al, 2015 ; Baldwin et al, 2011 ; Barnett et al, 2020 ; Fitzgerald et al 2017 ; Gray et al, 2016 ; Kenyon & Carter, 2011 ; Mohatt et al 2011 ; Snowshoe et al, 2017 ); and 10 were mixed methods studies (Clark et al, 2013 ; Gray et al, 2019 ; Harder et al, 2015 ; Ruttan et al, 2008 ; Pertucka et al, 2016 ; Ritchie et al, 2015 ; Sam et al, 2015 ; Stumblingbear-Riddle, 2012 ; Tiessen et al, 2009 ; Yeh et al, 2015 ). Community-consulted focus groups that used open-ended, semi-structured interviews were the most commonly used in qualitative and mixed-methods studies.…”
Section: Resultsmentioning
confidence: 99%
“…Quantitative studies focused primarily on the outcomes of mental health (particularly depressive symptoms, suicidal ideations), and protective factors measured at a single time point (Ames et al, 2015 ; Barnett et al, 2020 ; Gray et al, 2016 , 2019 ; Kenyon & Carter, 2011 ). Mental health was measured using validated questionnaires, primarily Centre for Epidemiologic Studies Depression Scale (Ames et al, 2015 ; Baldwin et al, 2011 ), WHO Survey of Health Behaviours in School-Aged Children (Ames et al, 2015 ), General-Self Scale of the March Self-Description Questionnaire (Ames et al, 2015 ), General Mattering Scale (Barnett et al, 2020 ), and Positive and Negative Affect Schedule (Barnett et al, 2020 ; Kenyon & Carter, 2011 ; Tiessen et al, 2009 ). In terms of promotive or protective factors, many studies used the Rosenberg self-esteem scale (Barnett et al, 2020 ; Gray et al, 2016 ; Harder et al, 2015 ; Tiessen et al, 2009 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation